Menggabungkan Tradisi dan Modernitas: Perbandingan Sistem Hukum dan Implikasi Pancasila - Lauw, Wifina; Thio, Ricky (Lex Aeterna Law Journal, 2023)
This research aims to analyze the relationship between various legal systems in the world and the values of Pancasila as Indonesia's fundamental principles. This research starts from the premise that a deep understanding of the differences and similarities between Civil Law and Common Law legal systems can provide new insights in applying Pancasila in a global context. The modern world requires states to accommodate various legal traditions while adapting to international practices. In Indonesia, the implementation of Pancasila values is often faced with the challenge of integration into a diverse global legal system. This phenomenon raises questions about how Pancasila can function in the context of a broad comparison of legal systems. This research aims to explore how the Civil Law and Common Law legal systems interact with the principles of Pancasila, and how this comparison can contribute to the development of inclusive and dynamic law in Indonesia. Comparative methods are used to analyze legal systems from various countries, with an emphasis on literature studies and normative analysis. Historical and philosophical approaches are also applied to understand the context and evolution of each legal system as well as the integration of Pancasila values. This study reveals that although there are substantial differences between the Civil Law and Common Law legal systems, there is room to integrate Pancasila values into each system. Pancasila not only acts as an ethical principle, but also as a framework for the formation of laws that are responsive and adaptive to global change, respecting domestic and international legal traditions.